Effects of different doses of canagliflozin on blood pressure and lipids in patients with type 2 diabetes: a meta-analysis. Issue 5 (25th May 2022) - Geng, Qiang; Hou, Fangjie; Zhang, Yonghuan; Wang, Zhengzhong; Zhao, Meiling
Abstract : Background: Canagliflozin is a sodium glucose-cotransporter-2 receptor inhibitor approved for the treatment of type 2 diabetes mellitus (T2DM). However, it is less prescribed due to increased LDL cholesterol (LDL-C), high incidence of urinary tract infection (UTI), high cost. Data on the effect of canagliflozin on blood pressure (BP) are also limited. We conducted a meta-analysis of randomized controlled trials (RCTs) to review dosedependent effects of canagliflozin on BP and lipids in patients with T2DM. Methods: A meta-analysis of RCTs in patients with T2DM was conducted. MEDLINE, the Cochrane Library of Trials and Clinicaltrials.gov were searched for relevant studies from January 2008 to May 2021. Results: Compared with placebo, canagliflozin 100 mg reduced SBP by 3.43 mmHg and DBP by 1.05 mmHg. Canagliflozin 100 mg increased LDL-C by 0.10mmol/l and HDL cholesterol (HDL-C) by 0.05 mmol/l. Compared with placebo, canagliflozin 300 mg reduced SBP by 4.75 mmHg and DBP by 1.69 mmHg. Canagliflozin 300 mg increased LDL-C by 0.16 mmol/l and HDL-C by 0.06 mmol/l. Compared with canagliflozin 100 mg, canagliflozin 300 mg further reduced SBP by 1.21 mmHg and DBP by 0.64 mmHg, and further increased LDL-C by 0.06 mmol/l and HDL-C by 0.02 mmol/l. Compared with placebo and canagliflozin 100 mg, canagliflozin 300 mg increased the risk of UTI. Conclusion: The current meta-analysis provides new evidence on different doses of canagliflozin as an antihypertensive agent in T2DM complicated by hypertension; however, LDL-C and the risk of UTI should be monitored.